The Price Effects of Spatial Competition - Ohta, H. (Review of Economic Studies, 1981)
Journal Article The Price Effects of Spatial Competition Get access H. Ohta H. Ohta Aoyama Gakuin University and University of Houston Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 2, April 1981, Pages 317–325, https://doi.org/10.2307/2296888 Published: 01 April 1981 Article history Received: 01 August 1979 Accepted: 01 August 1980 Published: 01 April 1981